2018
DOI: 10.30799/jespr.123.18040203
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals Charaterisation of Environmental Media (Soils, Water and Tree Barks) Around Cement Manufacturing Area, Nigeria

Abstract: The industrial activities remain a major source of pollution to environment. The impact assessment of Cement productions on the environmental media: soils, groundwater and tree barks was thus investigated. Forty (40) composite soils, ten (10) groundwater and six (6) tree barks samples were collected around Dangote Cement, Ibese, and West African Portland Cement Company (WAPCO), Sagamu, Nigeria, and were analysed of trace metals following standard procedure. The concentration of Fe, Cr and Pb in top soils (sub … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Furthermore, Oyetibo et al (2017) reported that road-dust and industrial atmospheric effluents discharged makes it easy to transfer appreciable significant toxic metals into wetland areas through precipitation. The high concentrations of these soils—(Cu, Zn and Cd) are of great concerns to the environment and may be attributed to poor community sewage system and abuse of fertilizer by farmers (Majolagbe et al, 2018; Y. Zhang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Oyetibo et al (2017) reported that road-dust and industrial atmospheric effluents discharged makes it easy to transfer appreciable significant toxic metals into wetland areas through precipitation. The high concentrations of these soils—(Cu, Zn and Cd) are of great concerns to the environment and may be attributed to poor community sewage system and abuse of fertilizer by farmers (Majolagbe et al, 2018; Y. Zhang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Air, Soil and Water Research into wetland areas through precipitation. The high concentrations of these soils-(Cu, Zn and Cd) are of great concerns to the environment and may be attributed to poor community sewage system and abuse of fertilizer by farmers (Majolagbe et al, 2018;.…”
Section: Concentration Of Heavy Metals In Ibese Wetland Soils Located...mentioning
confidence: 99%
“…Furthermore, air, noise, and soil quality indicators were below the Federal Environmental Protection Agency's acceptable standards, according to Ufuoma and Omoyeni (2017). Similarly, Majolagbe et al (2018) claimed that Co, Cr, Fe, Ni, and Pb levels in soils around cement plants are typical. Because metals are irreversible and have harmful impacts on living creatures, determining the heavy metal concentration of soils around cement plants should be part of the environmental monitoring and evaluation process.…”
Section: Introductionmentioning
confidence: 99%
“…Cement production is a high-energy process, and cement is the most expensive component among building materials. Added to that, the quantity of CO 2 produced by cement manufacturing is very significant . Fly ash (FA) has been considered an unsafe solid waste .…”
Section: Introductionmentioning
confidence: 99%
“…Added to that, the quantity of CO 2 produced by cement manufacturing is very significant. 1 Fly ash (FA) has been considered an unsafe solid waste. 2 The high amount of FA, derived from thermal power stations because of coal combustion, presents a serious environmental problem.…”
Section: Introductionmentioning
confidence: 99%